RISK MODEL OF PARTICIPATING LIFE ANNUITY (PLA) AND INVESTMENT - Citraningsih, Ai
Annuity is a form of payment transaction that is applied in the nancial sector. One application of annuities is the payment of pension benets. In general, the amount of annuity payments is always xed, but there are annuity products whose payments are not xed. One of them is the Participating Life Annuity (PLA) which is the standard annuity product in Germany. The PLA annuity consists of a guaranteed benet (MJ) and an additional benet (MTt). Additional benets are calculated from the investment prots made by the insurance company on the premiums received. Therefore, there is investment risk and risk of loss due to PLA payments. The risk of loss due to annuity payments is quantied and measured by Modied Annuity at Risk (MAaR) which is the largest loss value tolerated by the insurance company. The investment model used is the Binomial Model and the Geometric Brownian Motion Model. Three simulations were performed on each model, in order to obtain data on investment value, prot value, and loss value for PLA payments. The risk measures were calculated at the 10%, 5%, and 1% condence levels based on the simulation data.